Jewish-Muslim relations in past and present : a kaleidoscopic view - Meri, Josef W. (Studies on the Children of Abraham, 2017)
This volume assembles multidisciplinary research on the Judaeo-Islamic tradition in medieval and modern contexts. The introduction discusses the nature of this tradition and proposes the more fluid and inclusive designation of "Jewish-Muslim Relations." Contributions highlight diverse aspects of Jewish-Muslim relations in medieval and modern contexts, including the academic study of Jewish history, the Qur'anic notion of the "upright community" referring to the "People of the Book," Jews in medieval fatwas, use of Arabic and Hebrew script, Jewish prayer in Christian Europe and the Islamic world, the permissibility of Arabic music in modern Jewish thought, Jewish and Muslim feminist exegesis, modern Sephardic and Morisco identity, popular Tunisian song, Jewish-Muslim relations in cinema and A.S. Yehuda's study of an 11th-century Jewish mystic.